Social Workers’ Experiences of Public Perceptions of the Social Work Profession: An Exploratory Study - Kristofer Nilsson; Marie Nordfeldt; Evelina Landstedt (SAGE Open)
Public perceptions play a crucial role in shaping the image of any profession, and social work is no exception. It is widely assumed that adverse public views of social work can negatively impact the legitimacy of social services and the well-being of social workers—ultimately threatening efficiency and retention. Yet, empirical studies addressing these assumptions are rare. The current study investigates social workers’ experiences of public perceptions of the social work profession and key factors contributing to public views. Focus groups with Swedish social workers were conducted, and data were analysed via qualitative content analysis. The dirty work framework was applied in interpreting the findings. The analysis revealed that adverse public views are experienced as prevalent and that organisational structures, legislation, and social work practice contribute to such views. However, media portrayals are seen as the most influential factor in establishing adverse public views. Based on the social workers’ experiences, it is concluded that the social services in Sweden can be understood as socially and morally tainted, but that levels of taint differ between social services areas, and efforts to reduce such taint are discussed.